2021
DOI: 10.3390/land10040340
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Importance of a Footbridge Suspended over a Highway in the Opinion of Its Users—Trabzon (Turkey)

Abstract: In the urban landscape, footbridges appeared along with the development of urbanization through the implementation of more complex spatial structures. The introduction of transport transit to cities or sometimes urban gravity towards the important communication routes imposed their construction in order to ensure pedestrians’ safety and smooth flow of traffic. The aim of the study is to determine how an overpass in the city of Trabzon is used by people of different ages, the security and motivation problem, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To select areas with bad and good air quality, a quantitative method called the semantic differential (SD) was used, which examines the perception assessment of a phenomenon or object [ 51 , 52 ]. This method is often used in research related to the perception of various elements of human surroundings, e.g., the acoustic environment [ 53 ], the color of lighting in gardens [ 54 ], the quality of equipment in the public space [ 55 ], the attractiveness of the landscape [ 56 ], the thermal comfort [ 57 ], the visual contamination of the streets [ 58 ], safety in terms of pedestrian traffic in the cities [ 59 ] or the quality of green areas [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…To select areas with bad and good air quality, a quantitative method called the semantic differential (SD) was used, which examines the perception assessment of a phenomenon or object [ 51 , 52 ]. This method is often used in research related to the perception of various elements of human surroundings, e.g., the acoustic environment [ 53 ], the color of lighting in gardens [ 54 ], the quality of equipment in the public space [ 55 ], the attractiveness of the landscape [ 56 ], the thermal comfort [ 57 ], the visual contamination of the streets [ 58 ], safety in terms of pedestrian traffic in the cities [ 59 ] or the quality of green areas [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various studies on and measures of different aspects of development can be found in the literature (e.g. Przybyła et al, 2014;Przybyła et al, 2019;Kurtyka-Marcak, 2019;Hełdak et al, 2021;Moskowitz, 2021). Since the forms of data available are limited, particularly at the level of cities, the choice of measures is, by necessity, a compromise between the accessibility of the required data and their efficacy in assessing the aspects of economic development studied.…”
Section: Constructing a Measure Of A City's Socio-economic Developmentmentioning
confidence: 99%
“…As noted in [7][8][9][10][11][12][13][14], many in-service pedestrian bridges do not meet the conditions for comfortable usage, especially for people with physical disabilities, since the use of steep stairs or ramps is often required.…”
Section: Introductionmentioning
confidence: 99%